Pro iOS and android apps for business : with jQuery mobile, Node.js, and MongoDB - Zammetti, Frank (Apress Imprint: Apress, 2013)
With Pro iOS and Android Apps for Business, you can take your web development experience and apply it toward creating a full-featured business app, from soup to nuts. Frank Zammetti shows you how to create a client app using jQuery Mobile wrapped in PhoneGap, and how to create a node.js-based server that uses MongoDB as its data store. You never have to deal with learning Objective-C, Java or any other difficult-to-learn language. Instead, you can build on your existing HTML5, JavaScript and CSS experience to quickly and effectively build any app your business needs. You can apply this knowledge to iOS and Android apps as well as other mobile platforms since the technologies used support most modern mobile platforms as well. You'll learn: How to design a full-featured app, including requirements like offline access How to build the client-side of the app using jQuery Mobile, including adding stub code for calling the node.js server How to create a simple server with node.js and interact with it using REST How to use MongoDB with node.js for data storage How to use PhoneGap to ready your app for mobile deployment How to test and debug your app on iOS and Android Pro iOS and Android Apps for Business is for experienced web developers who need to get up to speed quickly in building iOS and Android apps for business. Are you ready to join the mobile revolution using the same technologies you already use to build great web applications? If so, this is the book for you!